What Drives Contagion : Trade Neighborhood, or Financial Links? - Valdes, Rodrigo (IMF Working Papers; Working Paper ;, 2001)
This paper presents evidence on the relative importance of alternative contagion channels during the Thai, Russian, and Brazilian crises. Results show that when crises are measured by changes in sovereign bond spreads, financial competition seems to explain almost all contagion episodes. However, when crises are measured by stock market returns, trade links and neighborhood effects appear to be relevant contagion channels during the Thai and Brazilian crises, while financial competition remains the only relevant channel in the case of the Russian crisis.